Remarks at International Conference on Improving Governance and Fighting Corruption, Brussels, March 14, 2007 - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed the fight for good governance and the fight against corruption. More and more African countries are taking on the challenge of corruption. It is important to work with the private sector to combat corruption in developing countries. It should be possible to work to strengthen systems in the country rather than trying to create parallel systems that bypass and, in the process, weaken indigenous systems. He noted the need to monitor progress and to work with donors on harmonization. A strong private sector creates jobs, opportunities for people to improve their own lives and even more importantly the lives of their children in honest work rather than in corruption. It is a virtuous circle where good governance leads to stronger development and stronger development leads to stronger governance.